IFT80, which encodes a conserved intraflagellar transport protein, is mutated in Jeune asphyxiating thoracic dystrophy - ELÇİOĞLU, HURİYE NURSEL (NATURE PUBLISHING GROUP, 2007)
Jeune asphyxiating thoracic dystrophy, an autosomal recessive chondrodysplasia, often leads to death in infancy because of a severely constricted thoracic cage and respiratory insufficiency; retinal degeneration, cystic renal disease and polydactyly may be complicating features. We show that IFT80 mutations underlie a subset of Jeune asphyxiating thoracic dystrophy cases, establishing the first association of a defective intraflagellar transport (IFT) protein with human disease. Knockdown of ift80 in zebrafish resulted in cystic kidneys, and knockdown in Tetrahymena thermophila produced shortened or absent cilia.
Keywords: REPRESSOR FUNCTIONS; C-ELEGANS; GENES; CILIA; ACTIVATOR; GLI